Natural Post-Disaster Management Archive Model - Izzul Fatchu Reza; Ridwan Rajab; Hamidah Rosidanti (Jurnal Good Governance, 2022)
As a country within the "ring of fire" geographical area, Indonesia is vulnerable to natural disasters. The impact of natural disasters is not only physical and human, but also relates to the records that are owned. This study strives to support efforts to save archives after natural disasters and develop a model for saving and restoring archives after natural disasters happens. The results of the research showed that there is no a standardized procedures to save and restore archive in times of disasters, therefore there shall be regulation to make the regional disaster agency, the regency offices, and library and archives agency coordinate and cooperate in a single task-force, based on our developed model.Keywords: disaster; archives; archive recovery